Racial and ethnic differences in bullying: Review and implications for intervention - Xu, Mariah; Macrynikola, Natalia; Waseem, Muhammad; Miranda, Regina (Aggression and violent behavior, 2020)
Despite increased research on bullying over the past few decades, researchers still have little understanding of how bullying differentially affects racial and ethnic minority and immigrant youth. To facilitate efforts to better evaluate the impact of bullying among racial and ethnic minority youth and improve interventions, we integrated research from multiple disciplines and conducted a systematic search to review relevant cross-cultural research on the prevalence of bullying, risk and protective factors, and differences in behaviors and outcomes associated with bullying in these populations. Studies measuring differences in bullying prevalence by racial and ethnic groups are inconclusive, and discrepancies in findings may be explained by differences in how bullying is measured and the impact of school and social environments. Racial and ethnic minorities and immigrants are disproportionately affected by contextual-level risk factors associated with bullying (e.g., adverse community, home, and school environments), which may moderate the effects of individual-level predictors of bullying victimization or perpetration (e.g., depressive symptoms, acculturation stress, attitudes toward aggression, etc.) on involvement and outcomes. Minority youth may be more likely to perpetrate bullying, and are at much higher risk for poor health and behavioral outcomes as a result of bias-based bullying. At the same time, racial and ethnic minorities and immigrants may be protected against bullying involvement and its negative consequences as a result of strong ethnic identity, positive cultural and family values, and other resilience factors. Considering these findings, we evaluate existing bullying interventions and prevention programs and propose directions for future research. •Bullying-related social-ecological factors disproportionately affect minorities.•Ethnic identity and cultural factors are protective for minorities.•Bias-based bullying poses greater health risks than non-bias-based bullying.•Cultural insensitivity in methodology may explain inconsistencies in findings.•Current interventions are less effective for minorities; future directions proposed.